The Internationalization of Taqwa Values in Framing Multicultural Education - Maman Maman; Yanti Nurdiyanti; Uus Ruswandi (Nazhruna: Jurnal Pendidikan Islam, 2022)
Internalization of religious values ​is needed so that religion always becomes the spiritual, moral, and ethical foundation in the lives of individuals, society, nation, and state, while respect for the diversity of religious understanding and practice is intended to encourage moderate religious life. Taqwa is one of the essences of religion that guides a person in carrying out his life. This research is library research. The source of this research data is the 2019 Ministry of Religion Moderation Book of Religion as the basis for the study, as well as books and research results related to taqwa values ​and multicultural education. Data analysis used the Milles and Huberman technique which consists of data collection, data reduction, and data presentation to conclude. The actualization of taqwa is carried out in the form of carrying out all His commands and staying away from everything He forbids. The values ​​of taqwa manifest in the form; Maintain a relationship with Allah SWT (Hablum Minallah), maintaining relationships with fellow human beings (Hablum Minannas), Relationships with oneself, and Relationships with the environment. The forms of internalization of taqwa in multicultural education are carried out in several ways; 1) Internalization in the learning process 2) Internalization through example and 3) Internalization through class culture, culture, school, and family culture.